THE STRATEGIES FOR THE DEVELOPMENT OF THE DIGITAL ECONOMY IN THE REPUBLIC OF UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2023)
The article discusses in detail the changes in the economic system, which is digitalization. The main factors in the development of the digital economy, the universal Internet, high communication, applications and services based on cloud technologies, big data analysis, automation, robotics, multi-channel or channel models for the distribution of goods and services are analyzed.